Manajemen Risiko Pada Penerapan Manajemen Rantai Pasokan Global: Kajian Terhadap Pendekatan Strategis Untuk Mengidentifikasi, Mengevaluasi, dan Mengelola Risiko - Rahayu Mardikaningsih; Siti Nur Halizah; Reny Nuraini; Didit Darmawan; Rommy Hardyansah (Fakultas Ekonomi Universitas Yos Soedarso, 2024)
Risk management in global supply chain implementation is very relevant in today's complex business environment. This study reviews strategic approaches to identifying, evaluating, and managing risks in global supply chains. Through a qualitative approach, this study considers risk management concepts, global supply chain strategies, as well as approaches that have been used in related literature. The objectives of this study include risk identification, evaluation methods, geopolitical risk management, operational efficiency, and the role of information technology. The results show that strategic approaches such as supply chain mapping, SWOT analysis and collaboration with suppliers can help identify and manage risks more effectively. Evaluation methods such as probability-impact analysis, HAZOP analysis, and failure tree analysis are used to evaluate risks in global supply chains. Managing risks related to geopolitical uncertainty and regulatory changes involves monitoring the external environment, diversifying supply sources, and collaborating with stakeholders. Implementing a strategic approach has a significant impact on the operational efficiency and sustainability of global supply chains by reducing uncertainty and increasing readiness to face risks. Information and communication technology plays an important role to support the implementation of this strategic approach by facilitating data collection and analysis and increasing the involvement of all stakeholders.